EFFECT OF ZIGZAG AND LINE PRINTING PATTERN ON TENSILE STRENGTH AND SURFACE ROUGHNESS OF FUSED DEPOSITION MODELING PRODUCT - Sari, Ayu Perwita; Rhohman, Fatkur; Winata, Ayis Nuredi; Herlanto, Frendy Edo; Lubis, Abdul Munir Hidayat Syah; Anggono, Agus Dwi (Universitas Muhammadiyah Surakarta, 2024)
This research aims to test the results of 3D printing using Polylactic acid (PLA) filament on surface roughness and tensile strength. Experiments were carried out by adjusting the differences in printing fill density for the pattern used. Filling density uses variations of 60%, 80%, and 100%. The tensile test is used to measure the tensile mechanical properties of polymers (σ). The roughness test is obtained to determine the average surface roughness (Ra), root mean square roughness (Rq), and ten-point height (Rz). The test specimen uses the ASTM D638 type 4 standard model and size. The nozzle diameter is 0.4 mm, the temperature is 220 °C, and the heat bed temperature is 60 °C. The mechanical properties test results of the printing pattern showed that the zigzag pattern had the highest yield strength, maximum load, and elongation values, namely 0.97 N/mm2, 52.99 N, and 9.43%. Meanwhile, in the line pattern, the highest yield strength, maximum load, and elongation values were 1.51 N/mm2, 62.72 N, and 3.54% and the highest yield of the two patterns was in the highest printing pattern, namely 100%. It was concluded that the larger the printing pattern, the wider the filament will be, as a, result the level of surface roughness will also be higher.